Aspects оf Using Social Media in Research - TUMANOV, O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
In recent years, there has been a rapid development of social media and a high interest in them by the population, which increases the opportunities for social research. This makes it relevant to discuss issues related to the use of social media as a source of reliable data for future research. The purpose of the article is to analyze the program-methodological and organizational foundations of the research using data from social media. The definition of the concept of “social media” is given; issues of classification of social media platforms and the applicability to the social media of such concept as “big data” are discussed. The goals of using social media in the public sector are defined and discussed: communication and interaction; analysis and research. Social media is described as a research tool. The life cycle of a study using social media is defined, which includes addressing the problems associated with determining whether a social query is the result of such research; the quality of data from sources such as social media; using tools for such research and publicizing its results; evaluation of its results. The ethical principles of conducting such research discussed in the article include: the proper application of social research methods and a scientifically sound interpretation of the findings obtained from them; participation based on informed consent; activation of participation; confidentiality in order to prevent personal and social harm. The information provided in the article will help raise awareness about research opportunities using social media.